Effects of a novel, non-invasive pre-hatch application of probiotic for broilers on development of cecum microbiota and production performance - Kasper Rømer Villumsen; Dorthe Sandvang; Gisle Vestergård; Mia Son Räfle Olsen; Johanne Juul; Morten Dencker; Johannes Kudsk; Louise Ladefoged Poulsen (Animal Microbiome, 2023)
Abstract Background Probiotics are used in the broiler industry to increase production performance. Most often a probiotic is applied by mixing it in the feed, but studies have shown that earlier application may be advantageous. Therefore, in ovo application where the probiotic is administrated into the egg before hatch has been investigated as an alternative application method. However, in ovo application may impact hatchability negatively and may not be feasible at all hatcheries. The purpose of this study was to investigate the effect of a novel non-invasive method for mass application before hatch. The probiotic (E. faecium 669) was applied as a single dose by spray on the unhatched eggs and production performance and development of the cecal microbiota until slaughter was compared with a control flock. Through 16S rRNA sequencing of cecal samples from 25 broilers at day 7, 21 and 37 we compared the microbiota composition and richness for each group. The study was repeated for additional recording of production performance and re-isolation of the probiotic E. faecium from the intestine. Results In both trials the probiotic E. faecium could be re-isolated from the yolk sac and intestine at hatch and at day 7. Broilers in the probiotic treated groups had a higher performance in terms of bodyweight at day 34 and European production efficiency factor. Finally, a significant reduction of first-week and overall mortality was observed in the probiotic group in the first trial. Based on 16S rRNA profiling, significant differences in alpha diversity were found exclusively at day 37. Estimation of beta diversities, however, identified significant differences in microbiota composition between the control and probiotic group at day 7, 21 and 37. Conclusion The probiotic E. faecium strain successfully colonized broilers before/during hatch after a single spray application at day 18 of incubation. Positive effects of the probiotic were observed in multiple production parameters, including reduced mortality in trial 1, and microbiota analyses indicate significantly different microbiota compositions throughout the experimental phase. Taken together, the novel low-tech mass administration of E. faecium (669) may be considered a feasible strategy for improvements of production parameters in broiler production.